Studies in Islamic history and institutions - Goitein, S. D., 1900-1985. (Brill Classics in Islam, 2010)
Goitein's selection of studies dealing with Islamic history, religion, and institutions offers a wide-ranging, sensitive, and highly original introduction to a civilization by one who lived all his life studying and observing Islam. Eschewing simplistic notions, Goitein poses fundamental questions vis-à-vis Muslim religious thought and practice, the evolution of the Islamic state in the early Middle Ages, the characteristic facets of the civilization, and the periodization of its history. Although all but one of the essays deal with the first seven centuries of Islamic history, Goitein frequently draws important connections between the past and the present. A professional educator as well as researcher and scholar, Goitein with a clarity and orderliness makes his subtly reasoned conclusions accessible to students and scholars alike. He provides the reader with an opportunity to acquaint himself not only with the results of research, but also with the methods by which they were obtained. With a new foreword by Norman A. Stillman.